Women's sexual function before and during COVID‐19 pandemic: A systematic review and meta‐analysis. Issue 9 (17th July 2022) - Hessami, Kamran; Sayegh, Nicolas; Abdolmaleki, Abolfazl S.; Bakht, Safoura; Qaderi, Shohra; Darabi, Mohammadhasan; Shamsi, Tahere; Bagheri, Fateme
Abstract: Background: To systematically review and summarize the available literature regarding the women's sexual function during COVID‐19 pandemic and compare it to pre‐pandemic period. Methods: We searched PubMed and Embase from the inception of the databases until 15th April 2021. Data regarding the sexual function, measured by female sexual function index (FSFI), of adult sexually active women were extracted from the eligible studies and compared between the before and during the COVID‐19 pandemic. The secondary outcome was the frequency of intercourse during pandemic time. The random‐effect model was used to pool the mean differences and corresponding 95% confidence intervals (CIs). Heterogeneity was assessed using the I 2 value. Results: Our search resulted in a sample of six eligible studies, which involved 1114 female participants. The total FSFI score among study participants during pandemic was 22.93 (95% CI: 19.26–26.59), which indicated a significant decrease in sexual function of women during pandemic as compared to pre‐pandemic time (mean difference = −3.80, 95% CI: −6.48 to −1.12, p = 0.005, I 2 = 96%). We also conducted a meta‐analysis of individual FSFI domains. During pandemic, women had problems with arousal ( p < 0.0001), orgasm ( p = 0.0008), satisfaction ( p = 0.0009), and pain ( p = 0.009). No significant difference in frequency of intercourse was observed between pre‐ and during pandemic ( p = 0.80). Furthermore, no significant publication bias was present among included studies. Conclusion: Overall, there was a significant decrease in sexual function of sexually active adult women during COVID‐19 pandemic. The most affected areas of sexual function were arousal, orgasm, pain, and satisfaction. Physicians must be aware of COVID‐19 impact on sexual life of women and provide proper counseling.